Damaging Effects of Total Parenteral Nutrition Formula on Vascular Endothelium. Issue 4 (October 2015) - Demircan, Mehmet; Gurunluoglu, Kubulay; Karaman, Abdurrahman; Mizrak, Bulent
ABSTRACT Objectives: Sepsis in one of the most serious complications that can occur during total parenteral nutrition (TPN) procedures. In this experimental study, we investigated the effects of TPN, with or without lipid emulsion, on vascular endothelial damage. Methods: In total, 50 rabbits were used, divided into 5 groups of 10 each. TPN with lipids (group 1), TPN without lipids (group 2), and 0.09% saline (group 3) were given for 10 days via a central venous catheter. Group 4 received no treatment other than placement of a central venous catheter for 10 days. Group 5 was a control group. At the end of day 10, rabbits were sacrificed and tissue samples of liver, kidney, and inferior vena cava were prepared and examined by immunohistochemical methods for vascular cellular adhesion molecule (VCAM)-1 expression. Results: In tissue sections of liver, kidney, and inferior vena cava, VCAM-1 activity was increased prominently in TPN with and without lipids compared with the control group. VCAM-1 activity in the TPN with lipids group was decreased versus the TPN without lipids group (P > 0.05). Conclusions: The TPN procedure results in vascular endothelial cell damage not only in the vein where the solution is introduced but also in other parts of the vascular system. Even if it is not statistically significant, lipids in the TPN formula may decrease this endothelial cell damage, as shown by immunohistochemistry.